Effect of Public Debt on Equity Prices - Henry, Marvin (Journal of Accounting and Finance, 2024)
With the growing debt harbored by the United States becoming harder to sustain, one believes it is imperative to research the effect of increases in public debt and events related to debt management policy on our financial system. In fleshing out this relationship, this paper can supplement the literature surrounding the development of nations through marketable debt products, the behavior of our financial markets and proper public debt management. This study considers the rationality of the market, as it is influenced by this exogenous variable over time, and how that relates to an equity’s price movements. Utilizing a vector-autoregression and structural vector-autoregression estimated with OLS, I will determine how events related to public debt affect equities.